Library Website as a Tool for Information Dissemination for Students At Mbarara University Of Science And Technology. - Kyomugisha, Adrine (Kabale University, 2024)
The study investigated the library website as a tool for disseminating information to students at Mbarara University of Science and Technology (MUST). The study aimed to: determine the role of the library website in information dissemination for students at the MUST library, identify challenges students face when using the library website, and propose solutions to these challenges. A descriptive research design was employed, collecting data through interviews, observation, and document analysis. Findings on the role of the library website revealed that it provides access to an online catalog, enabling students to search for books, journals, and other resources available in the library. Regarding challenges, students reported limited internet access, which hampers their ability to utilize online resources, search the catalog, or download materials from the website. To address these challenges, respondents suggested collaborating with the university's IT department to improve internet connectivity across campus, including establishing Wi-Fi hotspots in key areas. Additionally, assigning staff members to update website content regularly, providing training to ensure proficiency in the content management system, and emphasizing the importance of current information were recommended. The study also suggested making essential resources, such as e-books and articles, downloadable for offline access, along with clear instructions on how to download and use these materials.